2022
DOI: 10.21203/rs.3.rs-1322625/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phenotypic Diversity In Natural Populations of Docynia Delavayi (Franch.) Schneid.

Abstract: Docynia delavayi (Franch.) Schneid. is a wild fruit tree with high medicinal, edible, ecological, and ornamental values. This paper investigates the phenotypic diversity of nine traits in fruit and leaf from 17 Docynia delavayi natural populations. The results of coefficient of variation showed petiole length and leaf area contributed the highest mean coefficient of variation (CV = 36.85% and 43.71%, respectively), while fruit vertical diameter had the lowest contribution index (CV=12.17%). The principal compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Moreover, the phenotypic diversity of nine natural populations of Paeonia delavayi was studied by using 31 morphological indexes. It was found that the CV ranged from 3.22% to 76.12%, and the average CV among populations was 25.24% [ 52 ]. The degree of variation in 23 flowering phenology-related traits and 7 ornamental traits of tree peony observed in this study differed from a previous report, perhaps because of the differences in population size, plant materials, cultivar-group construction, and modulation traits.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the phenotypic diversity of nine natural populations of Paeonia delavayi was studied by using 31 morphological indexes. It was found that the CV ranged from 3.22% to 76.12%, and the average CV among populations was 25.24% [ 52 ]. The degree of variation in 23 flowering phenology-related traits and 7 ornamental traits of tree peony observed in this study differed from a previous report, perhaps because of the differences in population size, plant materials, cultivar-group construction, and modulation traits.…”
Section: Discussionmentioning
confidence: 99%
“…All in all, it is a wild resource that can be widely used as medicinal and edible with high development and utilization value (Wang et al 2022b(Wang et al , 2023b. Studies of D. delavayi have focused on various aspects, including asexual reproduction technology exploration (Liu and Hu 1984;Li et al 2019), biological characterization (Li et al 2010), transcriptomic and metabolomic analyses fruit metabolites (Wang et al 2022b;Chen et al 2022), molecular maker development and genetic diversity analysis (Peng et al 2020;Li et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…It has been applied to the systematic classification of species such as bryophytes [14], ferns [15][16][17], gymnosperms [18,19], and angiosperms [20][21][22]. Currently, research on tree peonies mainly focuses on morphology [23,24], palynology [2], cytology [25], molecular systematics [26,27]. Systematic observation on epidermal features of wild tree peonies leaves has not been reported.…”
Section: Introductionmentioning
confidence: 99%